2021
DOI: 10.12659/msm.932052
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CXCL13 as an Immune-Related Biomarker Associated with Tumorigenesis and Prognosis in Cutaneous Melanoma Patients

Abstract: Background Melanoma is one of the most lethal tumors and its treatment is still challenging. It is urgent to detect novel therapy targets in melanoma. Material/Methods The GEO dataset was used to obtain a list of DEGS (differentially-expressed genes). Integrative bioinformatics analyses, including HPRD database, TCGA data, and TIMER, were performed to determine the role of CXCL13 in SKCM (skin cutaneous melanoma) progression and the immune env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In addition, appropriate biomarkers should enable not only monitoring of the disease progression and response to treatment but also the early identification of individuals at high risk of metastases who may benefit from closer surveillance and adjuvant medicines (18,23). A study reported by Huang and Han et al primarily identified five chemokine members (CCL4, CCL5, CXCL9, CXCL10, CXCL13) as relevant biomarkers in cutaneous melanoma tumorigenesis and progression (24). Alimohammadi et al revealed that CXCR4 is implicated in the progression and metastasis of cutaneous melanoma (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, appropriate biomarkers should enable not only monitoring of the disease progression and response to treatment but also the early identification of individuals at high risk of metastases who may benefit from closer surveillance and adjuvant medicines (18,23). A study reported by Huang and Han et al primarily identified five chemokine members (CCL4, CCL5, CXCL9, CXCL10, CXCL13) as relevant biomarkers in cutaneous melanoma tumorigenesis and progression (24). Alimohammadi et al revealed that CXCR4 is implicated in the progression and metastasis of cutaneous melanoma (25).…”
Section: Discussionmentioning
confidence: 99%
“…A study reported by Huang and Han et al. primarily identified five chemokine members (CCL4, CCL5, CXCL9, CXCL10, CXCL13) as relevant biomarkers in cutaneous melanoma tumorigenesis and progression ( 24 ). Alimohammadi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, in our univariate analysis with segregated parameters for high and low values based on medians, we found no difference between TMB groups (Table S11). CXCL13 was suggested as a prognostic biomarker in melanoma before, but the correlation of ERCC3 with survival needs further validation (78,79).…”
Section: Discussionmentioning
confidence: 99%
“… 7 For ICB outcome prediction, the expression levels of genes associated with immune response mechanisms, from prior knowledge of cancer immunology, are commonly used. Those genes include known ICB targets ( CTLA4 , PD-1 , and PD-L1 ), cytokines and chemokines, 8 , 9 , 10 and genes involved in neoantigen presentation and immune-related biological pathways. 11 , 12 However, those genes have varied predictive effectiveness due to the large extent of inter- and intra-tumor heterogeneity and the complexity of the immune system.…”
Section: Gene Expression Signaturesmentioning
confidence: 99%